Synthesis of vertically aligned wafer-scale tantalum disulfide using high-Ar/H2S ratio plasma. (22nd October 2021) - Seok, Hyunho; Lee, Inkoo; Cho, Jinill; Sung, Dougyong; Baek, In-Keun; Lee, Cheol-Hun; Kim, Eungchul; Jeon, Sanghuck; Park, Kihong; Kim, Taesung
Abstract: Nanostructural modification of two-dimensional (2D) materials has attracted significant attention for enhancing hydrogen evolution reaction (HER) activity. In this study, the nanostructure of TaS2 films was controlled by controlling the Ar/H2 S gas ratio used in plasma-enhanced chemical vapor deposition (PECVD). At a high Ar/H2 S gas ratio, vertically aligned TaS2 (V-TaS2 ) films were formed over a large-area (4 in) at a temperature of 250 °C, which, to the best of our knowledge, is the lowest temperature reported for PECVD. Furthermore, the plasma species formed in the injected gas at various Ar/H2 S gas ratios were analyzed using optical emission spectroscopy to determine the synthesis mechanism. In addition, the 4 in wafer-scale V-TaS2 was analyzed by x-ray photoelectron spectroscopy, transmission electron microscopy, and atomic force microscopy, and the HER performance of the as-synthesized TaS2 fabricated with various Ar/H2 S ratios was measured. The results revealed that, depending on the film structure of TaS2, the HER performance can be enhanced owing to its structural advantage. Furthermore, the excellent stability and robustness of V-TaS2 was confirmed by conducting 1000 HER cycles and post-HER material characterization. This study provides important insights into the plasma-assisted nanostructural modification of 2D materials for application as enhanced electrocatalysts.